2012
DOI: 10.2478/10004-1254-63-2012-2218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of buffers for extraction of mite allergen der p 1 from dust

Abstract: Der p 1 is the main allergen of house dust mite Dermatophagoides pteronyssinus, which has routinely been detected in residential dust. However, the procedure for extracting Der p 1 from reservoir dust has not been well defi ned. The aim of this study was to compare Der p 1 mass fractions in dust extracts prepared using the following extraction buffers: phosphate (pH 7.4), borate (pH 8.0), and ammonium bicarbonate (pH 8.0), all with 0.05 % Tween 20. Twenty-eight dust samples were divided into three aliquots and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A recent article in this journal found that the type of extraction buffer did not affect measured levels of the major group one allergen (Der p 1) from the house dust mite, Dermatophagoides pteronyssinus, in household dust samples (1). This differed from a previous study where about twice the levels of Der p 1 were found in borate-buffered saline extracts, compared to ammonium bicarbonate buffer or phosphate-buffered saline extracts, irrespective of extraction temperature or time of extraction (2).…”
mentioning
confidence: 99%
“…A recent article in this journal found that the type of extraction buffer did not affect measured levels of the major group one allergen (Der p 1) from the house dust mite, Dermatophagoides pteronyssinus, in household dust samples (1). This differed from a previous study where about twice the levels of Der p 1 were found in borate-buffered saline extracts, compared to ammonium bicarbonate buffer or phosphate-buffered saline extracts, irrespective of extraction temperature or time of extraction (2).…”
mentioning
confidence: 99%